IDENTIFIKASI SPESIES POTYVIRUS PENYEBAB PENYAKIT MOSAIK PADA TANAMAN CABAI (Capsicum frutescens L.) MELALUI SIKUEN NUKLEOTIDA GEN Coat Protein - I Gede Rian Pramarta; I Gede Rai Maya Temaja; I Dewa Nyoman Nyana; Gede Suastika (Journal of Agricultural Science and Biotechnology, 2017)
Chili peppers (Capsicum frutescens L.) is one of the important vegetable in the world and one of the leading horticultural commodities in Indonesia. Pepper plants grown in all provinces in Indonesia and got priority for development because it has great potential economic value. These researches was conducted in order to determine the type of infecting Potyvirus on chili and know the proximity nucleotide sequence of Potyvirus infecting chili crop in Kerta village, Payangan, Gianyar, Bali, with the kind of Potyvirus in other areas. This study use RT-PCR technique to detect plant viruses and continued with tracing sequence coat protein gene nucleotide to its proximity to some of the isolates analyzed from GeneBank. The results showed that the infecting Potyvirus chili crop is Chili veinal motle virus species (ChiVMV) with size of approximately 900 bp DNA band, and based on phylogenetic analysis of coat protein gene nucleotide sequence, PayanganIndo isolate had high similarity (93%) and small genetic distance (0.041) with isolate of origin Thailand state.